JOB SATISFACTION AND INTENT TO LEAVE AMONG GRADUATE TEACHERS IN GOVERNMENT SCHOOLS IN SRI LANKA: SPECIAL REFERENCE TO JAFFNA DISTRICT - Kanojan, K.; Sivalogathasan, V. (University of Jaffna, 2017)
Job satisfaction is essential to employees to perform their dut ies effectively. Teachers’ job satisfaction and their intention to leave is not only important to teachers themselves but also it is very much essential to educational institutions and students as well. The purpose of this study was to find out the level of job satisfaction and intent to leave among Graduate Teachers in Government Schools in Jaffna District along with personal characteristics and job characteristics factors. This study was a quantitative approach and used the questionnaire for data collection. 200 graduate teachers participated. The findings indicated that the level of satisfaction of income, working condition and intrinsic reward was low, moderate, and moderate respectively. Also, these three independent variables influence teachers’ intention to leave. Further, this study found that personal characteristics such as; age, gender, marital status, and qualification and job characteristics such as teaching experience, present position, school level, subjects teaching and preferred subjects have no significant relationship with intention to leave. The results of this study support to achieve the organizational effectiveness by studying the impact of job satisfaction and intent to leave among graduate teachers in government schools, and suggest policies or practices that can be used to enhance the employee job satisfaction and organizational performance.
Keywords: Intent to leave; Job satisfaction; Work condition; Intrinsic rewards; personal characteristics; Job characteristics